Negative equity in the Irish housing market - Duffy, David (Economic & Social Studies, 2010)
Having peaked in early 2007 Irish house prices have fallen steadily. Negative equity occurs if house price falls result in the house value being lower than the outstanding debt. Many in negative equity will be unaffected and will continue to pay their mortgage without difficulty. Negative equity can increase the probability of defaulting if it occurs at the same time as cashflow problems, possibly caused by illness or job loss. This paper estimates that 116,000 borrowers were in negative equity at the end of 2009, rising to 196,000 borrowers by end-2010. Borrowing at, or close to the price peak, high loan-to-value ratios, interest only mortgages and longer mortgage terms have contributed to higher numbers in negative equity. First-time buyers are more likely to be experiencing negative equity. The research shows that many of those who have mortgages are employed in sectors where employment prospects, to date, remain relatively robust. Policies that assist households overcome a loss in income may help lower the default rate.
Policy paper
Keywords: Negative equity; Housing market; Ireland; House prices